Criteria for Appraising the Feasibility of Irrigation Projects Based on Findings and Conclusions of Evaluation Studies - Planning Commission (Planning Commission, 1965)
With a view to assessing the benefits of irrigation projects and finding more comprehensive criteria than the direct financial returns accruing to Government as the investing authority, the Planning Commission initiated in 1958 studies of five major well established irrigation projects, namely, Sarda Canal in the Punjab and U. P. region. Gang Canal in the Rajasthan and Madhya Pradesh region, Tribeni Canal and Damodar Canal in West Bengal, Bihar and Orissa region, and Cauvery-Mettur Project in the southern coastal region. These studies were carried out under a Committee of Direction headed by Prof. D. R. Gadgil and completed by the middle of 1961. The Committee worked for another two years on these studies, distilling detailed data for stimation of benefits in terms of selected criteria relating to increased productivity. This volume is their report, embodying the findings of the five evaluation studies and the Committee’s general approach for appraising the feasibility of irrigation projects.
Research Programmes Committee Planning Commission New Delhi 1965